Textbooks for English language teaching in public primary schools in Mexico and their correspondence with the official curricular approach - Pamplon-Irigoyen, Elva Nora; Ramírez-Romero, José Luis (Íkala, Revista de Lenguaje y Cultura, 2018)
This article presents findings from an analysis of textbooks used to teach English in public primary schools in Mexico. The analysis, which was part of a broader qualitative research study, focused on comparing the methodology used in the English and the Spanish course books that are part of the language area of the curriculum and share a sociocultural teaching approach. For this purpose, guidelines were defined using some of the elements which according to Richards & Rodgers (2009) characterize language teaching methods and approaches. The findings suggest that the textbooks used to teach English in the public primary schools do not adequately support or align with the sociocultural framework that is required by the official curriculum, in comparison to the Spanish textbooks. Based on this analysis, the article concludes with some considerations and recommendations about this topic and the professional development of the English teachers.